Optimal sizing of a stand-alone photovoltaic, wind turbine and fuel cell systems. (July 2020) - Khan, Asif; Javaid, Nadeem
Abstract: In this paper, Jaya algorithm is applied to find an optimal unit sizing of renewable energy resources, including photovoltaic (PV) panels, wind turbines (WTs), and fuel cells (FCs) with the objective of reducing the consumer's total annual cost in a stand-alone system. The system's reliability is considered using the maximum allowable loss of power supply probability ( LPSP max ) concept. The methodology is applied to real solar irradiation and wind speed data taken from Hawksbay, Pakistan. Simulation results achieved for low and high consumer's load profiles show that when LPSP max values are set to be 0% and 2%, the PV-FC is the most cost-effective system as compared to PV-WT-FC and WT-FC systems. Further, the results of Jaya algorithm are compared with a genetic algorithm, backtracking search algorithm, and particle swarm optimization.